2018
DOI: 10.22616/erdev2018.17.n106
|View full text |Cite
|
Sign up to set email alerts
|

Application case: prototype of radar tower structural health monitoring system

Abstract: Abstract. Industrial and civil structures like bridges, wind turbines, pipelines etc., are widely present in rural area. To maintain functionality of these structures, their condition is controlled using Structural Health Monitoring (SHM). SHM assists engineers in finding early structural defects like cracks, deformations, material deterioration, metal fatigue and so on. Monitoring can prevent accidents from happening by giving early warnings and a chance to perform necessary repairs and adjustments to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
4
Order By: Relevance
“…The sensing based on piezofilm sensors is a cost-effective SHM solution. They are much cheaper (about 10 euros/ piece) than accelerometers, which, for industrial applications, can cost hundreds of euros [36]. Accelerometers typically also induce mass loadings on structures and have a considerable size, thus affecting the modal and aerodynamic properties of structures.…”
Section: Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The sensing based on piezofilm sensors is a cost-effective SHM solution. They are much cheaper (about 10 euros/ piece) than accelerometers, which, for industrial applications, can cost hundreds of euros [36]. Accelerometers typically also induce mass loadings on structures and have a considerable size, thus affecting the modal and aerodynamic properties of structures.…”
Section: Propertiesmentioning
confidence: 99%
“…• a low maximum working temperature (100°C compared with 135°C for a copolymer film). The addition of preamplifiers to a sensing element allow for long measurement cables [35,36]. It has been shown that there is a considerable scatter of sensitivity of individual transducers in sensor networks; hence, sensors with preamplifiers are not optimal for precise measurements.…”
Section: Propertiesmentioning
confidence: 99%
See 3 more Smart Citations